Identification of Traffic-Induced Soil–Structure Resonance in Heritage Buildings and Mitigation using Operational Modal Analysis - Heri Khoeri; Dini Sofiana (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2026)
Excessive vibrations in heritage buildings located near heavy traffic often cause occupant discomfort despite adequate structural capacity. This study investigates the vibration mechanism and proposes a mitigation strategy with minimal intervention using Operational Modal Analysis (OMA) and Stochastic Subspace Identification (SSI). The identified fundamental frequency of the building is 3.09 Hz, which closely matches the dominant traffic-induced ground frequency (3.10 Hz), yielding a frequency ratio ≈ 1.0 and confirming soil–structure resonance as the governing mechanism. This resonance amplifies responses, particularly at intermediate floors. To mitigate the effect, a Multiple Tuned Mass Damper (MTMD) system with a total mass of 4 tons (≈0.54% of structural mass) is proposed. The MTMD effectively reduces dynamic amplification while remaining non-invasive, making it suitable for heritage structures. The results demonstrate that small-mass MTMD provides a practical and efficient vibration mitigation solution.